Maize yield, biomass and grain quality traits responses to delayed sowing date and genotypes in rain-fed condition - Fentuan Yang, Xiaoli Jiang, Qingjun Cao, Gang Li; Enping Zhang, Lamine Diallo; Kong, Fanli (Emirates Journal of Food and Agriculture, 2019)
Delayed sowing (DS) is a critical factor influencing grain yield and quality under climate change. This study was conducted to determine maize grain yield and quality traits responses to DS and varied genotypes in rain-fed condition, northeast of China. Two typical hybrids ZD958 (higher starch type) and LM33 (higher protein type) and three sowing dates: 30 April (DS0) as normal, 10 May (DS10) and 20 May (DS20) were compared. Results demonstrated maize grain yield, biomass, kernel number per square, thousand kernel weight (TKW), grain nutrition yield, N concentration and grain test weight were significantly reduced by DS. Compared to high protein type LM33, high starch type ZD958 had a higher yield potential and lower yield reduction with delayed sowing. Grain yield loss under DS could be mainly attributed to reduction of the BMP and biomass, thereby leading to the reduction of TKW and kernels number per unit. DS didn’t affected grain nutritional content (starch, protein and oil), while significantly reduced grain nutrition yield of starch, oil and protein with delayed sowing. This study suggests that, early sowing should be recommended to the framers and varieties adjustments maybe a possible approach to reduce and compensate for the loss of yield caused by delayed sowing in rain-fed condition under climate change in NCP.